Editorial: Behind the findings. Reflecting on research challenges - Clemente, M. (2019)
In light of our and other research experiences, we focus on and discuss some central dilemmas and challenges that can come across the different moments of the field research. Often remaining secondary in sociological accounts, these issues refer to the crucial process of getting and negotiating access to the field, the challenges raised by the intricate and multiple nature of relationships during the research process and, finally, different aspects related to the analysis and interpretation of data. Different research experiences in different socio-historical contexts underlines a set of basic ideas: that all research processes involve social interaction, even if in different degrees; that, as in any other social interaction, research takes place in social contexts and produces social effects; finally, that reflexivity is essential to acknowledge and control possible bias. Far from being a constraint, the awareness of such effects is the very condition for the production of knowledge. Reflexivity is a fundamental epistemological, methodological and ethical surveillance tool aimed at assuring conditions for productive exchanges and meaningful results.